Analisis Permintaan dan Pendugaan Efisiensi Tataniaga Ayam Ras Broiler pada Tingkat Produsen Di Kabupaten Mesuji - Lailatul Nasih; Toto Gunarto (Journal on Education, 2024)
This study aims to determine the variable price of broiler chickens, prices of other goods (Fish), gross income and consumer appetite for the amount of demand for broiler chickens in Way Serdang sub-district and to determine the level of commercial efficiency at the producer level and the efficiency of inter-level commerce. The research method used is a quantitative descriptive approach that explains the demand for broiler chickens and commercial channels and commercial institutions and to calculate and explain the inter-pordusen and margin trade margins By using primary data obtained from direct interviews with respondents at the research location, secondary data obtained from agencies or institutions related to this study such as the Central Statistics Agency (BPS) of Mesuji Regency and the Livestock Office.and research is descriptive analysis is carried out by calculating the amount of demand for chickens.